High-performance Ag2Se-based thermoelectrics for wearable electronics - Lin Zhang; Xiao-Lei Shi; Hongjing Shang; Hongwei Gu; Wenyi Chen; Meng Li; Daxing Huang; Hao Dong; Xiaolei Wang; Fazhu Ding; Zhi-Gang Chen (Nature Communications)
Abstract Flexible thermoelectric materials and devices hold enormous potential for wearable electronics but are hindered by inadequate material properties and inefficient assembly techniques, leading to suboptimal performance. Herein, we developed a flexible thermoelectric film, comprising Ag2Se nanowires as the primary material, a nylon membrane as a flexible scaffold, and reduced graphene oxide as a conductive network, achieving a record-high room-temperature ZT of 1.28. Hot-pressed Ag2Se nanowires exhibited strong (013) orientation, enhancing carrier mobility and electrical conductivity. Dispersed reduced graphene oxide further boosts electrical conductivity and induces an energy-filtering effect, decoupling electrical conductivity and the Seebeck coefficient to achieve an impressive power factor of 37 μW cm−1 K−2 at 300 K. The high-intensity between Ag2Se and reduced graphene oxide interfaces enhance phonon scattering, effectively reducing thermal conductivity to below 0.9 W m−1 K−1 and enabling the high ZT value. The nylon membrane endowed the film with exceptional flexibility. A large-scale out-of-plane device with 100 pairs of thermoelectric legs, assembled from these films, delivers an ultrahigh normalized power density of >9.8 μW cm−2 K−2, outperforming all reported Ag2Se-based flexible devices. When applied to the human body, the device generated sufficient power to operate a thermo-hygrometer and a wristwatch, demonstrating its practical potential for wearable electronics.